Covariates of hazardous alcohol use among sexual and gender minorities in Texas: Identifying the most vulnerable. (June 2020) - Wilkerson, J. Michael; Di Paola, Angela; McCurdy, Sheryl; Schick, Vanessa
Highlights: Hazardous drinking is common among sexual and gender minorities in Texas. More Hispanics with history of incarceration engaged in hazardous drinking. A recent depression diagnosis is inversely associated with hazardous drinking. Abstract: Background: Information is limited on the prevalence of hazardous drinking and associated covariates among sexual and gender minority (SGM) persons. These analyses estimated the prevalence of hazardous drinking and identified associated covariates. Methods: A total of 1273 SGM adolescents and adults living in Texas completed an online survey between March 2016 and January 2017. Variables associated with hazardous drinking at the bivariate-level (p < 0.10) were entered into multiple logistic regression models to estimate the strength of their association. Results: More than a third (39.1%) of participants meet criteria for hazardous drinking. Compared to non-hazardous drinkers, hazardous drinkers were younger ( x -  = 20.7 [SD = 8.9] vs. x -  = 26.5 [SD = 13.8]) and more likely to be Hispanic (41.5% vs. 26.2%). Hazardous drinkers were more likely to report using substances in past 12 months, including opioids (15.3% vs. 6.7%), stimulants (26.3% vs. 12.7%), and marijuana (37.6% vs. 21.2%). More hazardous drinkers reported injecting drugs (12.3% vs. 5.8%) and having a history of incarceration (14.1% vs. 7.3%). They were less likely to be diagnosed with depression (50.2% vs. 56.5%). When entered into a multivariate logistic regression model, hazardous drinkers were more likely to be younger (aOR = 0.97 [0.95, 0.98]), Hispanic (aOR = 1.5 [1.2, 2.0]), have a history of incarceration (aOR = 2.4 [1.5, 3.6]), and use a substance, not including marijuana (aOR = 1.7 [1.3, 2.3]). They were less likely to be diagnosed with depression (aOR = 0.73 [0.6, 0.9]). Conclusions: Our findings highlight the intersection of race and ethnicity, mental health, criminal justice involvement, and substance use and the need for tailored interventions that address underlying determinants.